Handwashing knowledge, attitudes, and practices during the COVID-19 pandemic in Saudi Arabia: A non-representative cross-sectional study - Osama Al-Wutayd (Nature Portfolio, 2021)
Abstract Handwashing (HW) with water and soap is one of the cheapest and most effective ways of protecting oneself and others against the coronavirus. Here, the HW knowledge, attitudes, and practices of Saudi adults were assessed during the COVID-19 pandemic using a cross-sectional study conducted between May 8 and June 8, 2020, during a partial lockdown period. A web-based validated questionnaire was distributed through different social media platforms, and the sociodemographic characteristics of the participants, seven items related to knowledge, four items related to attitudes, and thirteen items related to the practice of HW were assessed. A total of 1323 (51% male and 49% female) adults from all regions of Saudi Arabia responded to the questionnaire. The overall mean (± SD) was 5.13 (± 1.18) for knowledge of HW and COVID-19, 2.79 (± 0.77) for attitude toward HW, and 7.8 (± 2.56) for HW practice. A multiple linear regression analysis revealed factors associated with knowledge to be age and family income. Sex, educational level, family income, and HW knowledge were associated with negative and neutral attitude, whereas age, sex, family income, and HW knowledge were associated with practice. These results suggest that HW knowledge was strongly associated with positive attitudes toward HW and correct HW practice in Saudi adults during the COVID-19 lockdown.